Chronos, Locus und Kultur: Medialisierung von Zeit-, Raum- und Ortsreferenzen in Public-Health Diskursen - Feyrer, Cornelia (Linguistik Online, 2026)
Most institutions that launch health or social welfare campaigns as well as companies performing pharmaceutical advertising in a larger scope have to operate across languages and cultures. In this context there is always a certain mediatization and hybridization in the field of text and media genres showing enhanced allusions to time and location references. Precisely this genre lives from the unique fact that information and messages are designed in a way to make them understood and cognitively processed in fractions of a second – a challenge requiring tailor-made accurate target group orientation. For this reason, the focus of interest concerning orientation patterns is moving more and more to sociological and social psychological perspectives such as neurolinguistic programming strategies, which are – with a view to culture contact phenomena, internationalization and localization – absolutely relevant for intercultural encounters and communication and therefore for translation.This contribution aims – using selected formats from the fields of health communication, especially marketing and social welfare campaigns, from the hispano- and germanophone market – to show the extent to which time and location references as cultural specifics and elements of risk communication serve as instruments for emotionalization and target group-specific individualization of contents carving out the challenges for language and culture transfer as well as translation in this perspectivation.